Differential Effects of a Novel Opioid Ligand UTA1003 on Antinociceptive Tolerance and Motor Behaviour - Alok K. Paul; Krystel L. Woolley; Mohammed Rahmatullah; Polrat Wilairatana; Jason A. Smith; Nuri Gueven; Nikolas Dietis (MDPI AG, 2022)
Analgesic tolerance is a major problem in the clinic for the maintenance of opioid-induced long-term pain relief. Opioids with mixed activity on multiple opioid receptors promise reduced antinociceptive tolerance in preclinical studies, but these compounds typically show poor bioavailability upon oral, subcutaneous, intraperitoneal, or intravenous administration. We designed UTA1003 as a novel opioid that acts as a mu (MOP) and kappa (KOP) opioid receptor agonist and a partial agonist for delta (DOP) opioid receptor. In the present study, its antinociceptive effects, as well as its effects on antinociceptive tolerance and motor behaviour, were investigated in male rats. Acute antinociception was measured before (basal) and at different time points after subcutaneous injection of UTA1003 or morphine using the tail flick and hot plate assays. Various motor behavioural activities, including horizontal locomotion, rearing, and turning, were automatically measured in an open-field arena. The antinociceptive and behavioural effects of repeated administration of UTA1003 and morphine were determined over eight days. UTA1003 induced mild antinociceptive effects after acute administration but induced no tolerance after repeated treatment. Importantly, UTA1003 co-treatment with morphine prevented antinociceptive tolerance compared to morphine alone. UTA1003 showed less motor suppression than morphine in both acute and sub-chronic treatment regimens, while it did not affect morphine-induced motor suppression or hyper-excitation. Based on these activities, we speculate that UTA1003 crosses the blood-brain barrier after subcutaneous administration and, therefore, could be developed as a lead molecule to avoid opioid-induced antinociceptive tolerance and motor suppression. Further structural modifications to improve its antinociceptive effects, toxicity profile, and ADME parameters are nevertheless required.